The adventures of Beekle : the unimaginary friend [book with audioplayer] - Santat, Dan (VOX Books, 2018)
This magical story begins on an island far away where an imaginary friend is born. He patiently waits his turn to be chosen by a real child, but when he is overlooked time and again, he sets off on an incredible journey to the bustling city, where he finally meets his perfect match and--at long last--is given his special name: Beekle. The #1 New York Times bestselling and award-winning author and illustrator Dan Santat--creator of After the Fall and Are We There Yet? --combines classic storytelling with breathtaking art in an unforgettable tale about friendship, imagination, and the courage to find one's place in the world.